Misogyny and Misandry: Reasons and Mitigating Strategies in the Sample of Antenatal Patients in Tertiary Health Facilities in Owerri Municipal Imo State, Nigeria - Oparah, J.S; Fidelis, Mary Ndubuisi (International Journal of Human Kinetics, Health and Education, 2023)
This study investigated reasons and mitigating strategies for misogyny and misandry in a sample of antenatal patients in tertiary health facilities in Owerri Municipal, Imo State, Nigeria. A descriptive cross-sectional survey design was employed to carry out the study. The population consisted of antenatal patients accessing health services at Federal Medical Centre Owerri within the period of the administration of the questionnaire which lasted for two weeks. The sample size was 350 patients drawn randomly. A structured 25-item misogyny and Misandry: Reasons and Mitigating strategies Questionnaire (MMRMSQ) served as the instrument for data collection. Means and standard deviations were used to answer the research questions. Results showed that superiority complex shown by male health care givers, sexual abuse, differentiated treatment, unfaithfulness in relationship, cultural norms and religious beliefs are some of the reasons for misandry while aggression, neglect from female antenatal care givers, abusive treatment both in words and action are some of the reasons for misogyny. Health education, creating awareness, positive change in behavior and faithfulness in relationship were some of the identified mitigation strategies for misogyny and misandry. Findings suggested planning and implementing gender bias-free antenatal services by antenatal service providers and hospital management to avoid differentiated treatment; promote acceptance of gender diversity in the medical and paramedical profession and health education of antenatal patients by health educators on the consequences of misogyny and misandry on pregnancy outcome, and importance of good relationship skills in accessing antenatal care services. The aim of this education is to promote patronage of antenatal services among pregnant women, eventual improved delivery as well as maternal and child health.